SISTEM PAKAR IDENTIFIKASI PENYAKIT PERNAFASAN MENGGUNAKAN METODE CERTAINTY FACTOR (STUDI KASUS: RS.KURNIA CILEGON ) - Asep Mabrur Aid; Anita Megayanti; Penny Hendriyati (LPPM Unbaja, 2021)
Expert System is an information system that contains knowledge from experts so that it can be used for consultation. The knowledge of the experts in this system is used as a basis by the Expert System to answer the question (consultation). As a manifestation of the participation of the world of health in the development of technology, Expert System is also created to identify respiratory illness in facilitating the work of doctors in identifying the patient's illness. With Certainty Factor method, Expert System created can obtain 70% or more identification accuracy.